2015
DOI: 10.4172/2165-7556.1000136
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Discomfort

Abstract: A review of literature on comfort and discomfort indicates an increase in physical discomfort during the workday. In this paper, three different types of occupations were studied to identify whether a similar discomfort pattern exists in these occupations while participants perform work throughout the work day and workweek. Results are that sedentary and labor intensive occupations show an increase in physical discomfort throughout the workday. In addition, during the workweek, each occupation had a peak disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…However, the changes that Bazley et al. () reported were small, and the results can still be generalized to indicate that a neutral position was perceived to be more comfortable. Furthermore, the objective and subjective data indicated the same outcomes.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, the changes that Bazley et al. () reported were small, and the results can still be generalized to indicate that a neutral position was perceived to be more comfortable. Furthermore, the objective and subjective data indicated the same outcomes.…”
Section: Discussionmentioning
confidence: 83%
“…Bazley et al. () found that the basic discomfort pattern can fluctuate over such a time span, that is, a different time of day or a different day of the week could lead to a different comfort perception by study participants. However, the changes that Bazley et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that comfort experiences varies over time have been described before. Discomfort increases during the workday [12] and discomfort experiences increases significantly within the first two hours of sitting in a business class seat [13]. Theoretically, this pattern in discomfort or comfort in time could help prioritizing the aspects that need attention.…”
Section: Introductionmentioning
confidence: 99%
“…Bazley et al [25] demonstrated that in many jobs discomfort is high in the middle of the week and lowest at the beginning and end of the week. In addition, during the day the discomfort increases.…”
Section: Environmental Experiences Through Timementioning
confidence: 99%